1990
DOI: 10.1159/000150147
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Herpes Simplex Virus 1 Internal Repeat Sequences in Pathogenicity

Abstract: Three independently isolated herpes simplex virus type 1 recombinant viruses containing a deletion of approximately 14 kilobase pairs, representing greater than 95% of the internal repeat DNA sequences, were analyzed for their pathogenicity in mice. The recombinant viruses were found to be avirulent, exhibiting drastically increased LD50 values over wild-type herpes simplex virus 1(F) by intracerebral injection, nonneuroinvasive, unable to spread from the cornea to sensory ganglion, and unable to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…These mutant forms of the genomes of HSV-1 and CMV and now EHV-1 that fail to undergo isomerization are capable of replication in cell culture with an efficiency similar to that of wild type virus. However, the v11LΔIR mutant exhibited a significant reduction in pathogenicity in the mouse, and these findings are similar to the situation with the noninverting HSV-1 mutant that was found to be profoundly attenuated in vivo (Jenkins et al,1996; Jenkins and Martin, 1990). Since the vL11ΔIR has reduced virulence in vivo , it would be of interest to ascertain if this mutant virus has the ability to spread to the central nervous system and/or establish latency in the natural host.…”
Section: Discussionsupporting
confidence: 64%
“…These mutant forms of the genomes of HSV-1 and CMV and now EHV-1 that fail to undergo isomerization are capable of replication in cell culture with an efficiency similar to that of wild type virus. However, the v11LΔIR mutant exhibited a significant reduction in pathogenicity in the mouse, and these findings are similar to the situation with the noninverting HSV-1 mutant that was found to be profoundly attenuated in vivo (Jenkins et al,1996; Jenkins and Martin, 1990). Since the vL11ΔIR has reduced virulence in vivo , it would be of interest to ascertain if this mutant virus has the ability to spread to the central nervous system and/or establish latency in the natural host.…”
Section: Discussionsupporting
confidence: 64%
“…That is to say that peripheral replication of HSV may induce a non-permissive environment for viral replication in neurons innervating the site of replication. Animal models using corneal infections, have demonstrated that infectious HSV is not detected within trigeminal ganglia until 48 ± 72 h post-infection (Coen et al, 1989;Jenkins and Martin, 1990;Tenser and Edris, 1987). This delay would allow for the establishment of a IL-1/NGF/Oct-2-mediated non-permissive environment.…”
Section: A Viral Vector For Gene Therapymentioning
confidence: 99%
“…Recombinant mutants of HSV-1 that are not able to undergo homologous recombination due to the deletion of part or all of the inverted repeats at the junction between the L and S fragments (a=b=/a=c=) showed lower efficiency of replication in vitro than the corresponding wild-type virus and an absence of acute infection in vivo (27,28,41,46). These observations suggest that either the doubled rate of synthesis of proteins encoded by the b=a=/a=c= sequences and/or the ability to undergo homologous recombination is required for efficient in vivo infection.…”
mentioning
confidence: 99%